Line blot and western blot immunoassays for diagnosis of Mediterranean spotted fever. - Raoult, D (1989)
The line blot, a new immunoassay in which antigens are placed on nitrocellulose as narrow lines, was evaluated for its sensitivity and specificity relative to the microimmunofluorescence assay for the diagnosis of Mediterranean spotted fever (MSF). The line blot assay was only slightly less sensitive and less specific than the microimmunofluorescence assay for detection of immunoglobulin M (IgM) or IgG in 100 serum specimens from 42 patients with MSF. No line blot reactions were observed among 50 control serum specimens from febrile patients with other illnesses. The line blot assay was largely group reactive for spotted fever rickettsiae, but 26% of the positive serum specimens also cross-reacted by IgM with Rickettsia typhi. Western immunoblotting was used to characterize the antigenic components recognized by 19 MSF serum specimens. For both IgM and IgG, lipopolysaccharide was the cross-reactive group antigen, whereas the high-molecular-weight species-specific protein antigens (SPAs) were the only reactive proteins. Relative to the other nine rickettsiae, Rickettsia bellii was unique both in exhibiting no SPA reactions and in having a lipopolysaccharide with a predominantly high-molecular-weight distribution. Although most of the 19 MSF serum specimens examined by Western blotting exhibited preferential reactivity to SPAs of two strains of R. conorii and weaker reactions to the other rickettsiae, 2 serum specimens exhibited SPA reactions consistent with typhus infections. In comparison with other assays, the line blot and Western blot immunoassays have advantages which may permit an improvement in the general availability and commercialization of assays for the serodiagnosis of rickettsial infections.